How to cheat at designing a Windows server 2003 : active directory infrastructure - Craft, Melissa; Cross, Michael, 1965-; Kurz, Hal; Barber, Brian ("How to cheat--", 2006)
Windows 2003 Server is unquestionably the dominant enterprise level operating system in the industry, with 95% of all companies running it. The book will start off by teaching readers to create the conceptual design of their Active Directory infrastructure by gathering and analyzing business and technical requirements. Next, readers will create the logical design for an Active Directory infrastructure. Here the book starts to drill deeper and focus on aspects such as group policy design. Finally, readers will learn to create the physical design for an active directory and network Infrastructure including DNS server placement; DC and GC placements and Flexible Single Master Operations (FSMO) role placement.